Chronology of the development of active queue management algorithms of RED family. Part 3: from 2016 up to 2024 - Ivan S. Zaryadov; Hilquias C.C. Viana; Anna V. Korolkova; Tatiana A. Milovanova (Discrete and Continuous Models and Applied Computational Science, 2024)
This work is the first part of a large bibliographic review of active queue management algorithms of the Random Early Detection (RED) family, presented in the scientific press from 1993 to 2023. The third part will provide data on algorithms published from 2016 to 2023.